Apendisitis Akut dalam Kehamilan: Laporan Kasus - Utomo, Yudha Prasetyo; Wasistha, Farrel Uttu; Parinding, Immanuel Taba (PT Kalbe Farma Tbk., 2025)
Introduction: Acute appendicitis is the most common cause of non-obstetric surgical disease in pregnant women. However, clinical fndings may not be typical during pregnancy. The diagnosis of acute appendicitis in pregnancy is not straightforward as clinical signs may be mistaken for pregnancy-related symptoms. Case: An 18-year-old female G2P1A0, 10 weeks pregnant with lower middle abdominal continuous pain for 5 hours with nausea and vomiting twice and incomplete micturition. Vaginal bleeding and amniotic fuid discharge were ruled out. Physical examination revealed decreased bowel sounds, tenderness in the hypogastric, right iliac, and McBurney points, positive Dunphy, Psoas, and Obturator signs. With an Alvarado score of 7 and ultrasound results, acute appendicitis was diagnosed. An appendectomy was performed. Histopathological fndings suggest acute suppurative appendicitis. Conclusion: Appendicitis in pregnancy requires rapid and accurate diagnosis because the clinical symptoms are often considered to be symptoms of pregnancy.